Tahlil kitab At-ta’liimi Al lughah Al Arabiyah lis Shofi Al Ashir bil Madrasah Atsanawiyah bi Wizaroti Asyuúni Addiniyah fi Jumhuuriyah Indonesia - Khikam, Mohammad A'lal; Sunarko, Asep; Sholihah, Fitri; Rois, Ahmad; Mousa, Yousif (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
This thesis aims to: 1) to know what is the feasibility of the contents of the Arabic language textbook for tenth graders of Madrasah Aliyah, published by the Ministry of Religion of the Republic of Indonesia in 2020. 2) to know what is the feasibility of the presentation of the that textbook. 3) to know what is the feasibility of the language of the that textbook. 4) to know what is the feasibility of the graphics of the that textbook. This thesis uses a qualitative descriptive research approach where the type of research is library research. Data collection techniques using the method of documentation and searching on the internet. Then the data sources were obtained from primary data sources and secondary data (references related to writing Arabic textbooks, articles in journals, and Arabic dictionaries). The analysis technique used is the content analysis. The result show that: 1) Based on the eligibility of the content, the material presented in this book is in accordance with the core competencies and basic competencies in the Madrasah Aliyah curriculum number 183 of 2019. The material presented in this book is accurate in terms of concepts, definitions, principles, procedures, examples, facts and questions. But in the supporting material in this book there are no current references used. 2) Based on the feasibility of presentation, the presentation techniques in this book are in accordance with the indicators determined by the BSNP. The presentation of learning from this book is centered on students, prioritizing process skills, and prioritizing work safety. As for the completeness of the presentation, the contents of this book are complete, while the introduction and closing sections are still incomplete. 3) Based on the feasibility of language, the language used in this book is official Arabic, this book also provides a collection of vocabulary arranged in Arabic alphabetically and the meaning of using Indonesian, besides that this book also provides Arabic grammar exercises. As for chapter one and other chapters arranged harmoniously. 4) Based on graphic feasibility, the size of the book is in accordance with the international standard organization. Book cover designs are made with harmonious colors and sizes. As for the design, the contents of this book are displayed in a proportional and harmonious manner, but all the illustrations presented have not included a description of the image